The association between sleep duration and myopia among Chinese school-age students: mediation effect of physical activity - Feng, Haiqing; Gao, Yuexia; An, Na; Lu, Yitong; Huang, Jianping; Yang, Weiping; Lu, Qingyun (Frontiers in Public Health, 2025)
BackgroundThis study aimed to investigate the relationship between sleep duration and myopia in school-age students, as well as to observe the role of physical activity as a mediating variable in sleep duration and myopia.MethodsUsing multistage stratified sampling, 26,020 school-age students in Jiangsu Province, ages 7–18, were selected for this cross-sectional survey. Each participant completed a standardized interview in which their were asked about their vision, level of physical activity and average hours of sleep per day over the past month. Visual acuity examinations were conducted by the testing team’s ophthalmology professionals and they were categorized into two groups based on pre-set criteria: myopic and non-myopic. Sleep duration was classified into 3 categories: <8 h/d, 8–10 h/d, >10 h/d. The Pearson’s chi-square tests were used to examine differences in the incidence of myopia among participants. Binary multifactorial logistic regression adjusted for potential confounding variables was used to examine the relationship between myopia and a variety of factors. The mediating effects of physical activity on sleep duration and myopia were analyzed using the AMOS model.ResultsIn this study, the incidence of myopia was higher in females than in males, it also increased with age. Those who slept for <8 h/d had the greatest myopia rate (85.69%) compared with those who slept for≥8 h/d (p < 0.001). Sleep duration was found to be adversely correlated with myopia (sleep duration = 8–10 h/d: OR = 0.68, p < 0.01; sleep duration > 10 h/d: OR = 0.48, p < 0.01) after controlling for potential confounders like gender, age, and BMI-z score (Body Mass Index Score). Physical activity at a high intensity not moderate intensity was found to be protective factor against myopia. High-intensity physical activity also acted as a mediator in the negative association between sleep duration and myopia (a, b, c’ all p < 0.05).ConclusionThere is a negative correlation between sleep duration and myopia in school-age students, and that high-intensity physical activity mediates the relationship between sleep duration and myopia.